Perception of Quality Service among Customers of Deposit Money Banks in Dutsinma Local Government Area, Katsina, Nigeria - Mamman, Aliyu (British Journal of Marketing Studies, 2017)
The study sought to determine Perception of quality service among customers of Deposit Money Banks (DMBs) in Dutsinma Local Government Area, Katsina, Nigeria. The objective of the study is to determine customers’ perception of quality service from the point of view of; tangibility and reliability of the services; responsiveness and assurances of the banks to their customers. Secondary and primary sources were used in generating data for the study. Using stratified and random sampling techniques, the primary data was collected by means of a structured questionnaire administered to 380 customers of the three DMBs in the study area. Descriptive as well as inferential statistics (Regression Analysis) were used in analyzing the data collected from the respondents. The study found that the responsiveness aspect of the banking services has the highest impact on perception of quality service among customers of DMBs in the study area. This is followed by tangibility and reliability aspects of the services. The assurance aspects of the said banking services have the least impact on perception of quality service among the customers. Based on the findings, the study recommended that the three DMBs in Dutsinma Local Area should place more emphasis on the aspects of responsiveness and tangibility in their advertisement and physical interaction with their customers.